Impact of Cooperative, Flipped Digitalized Classroom on the Attitude of Male and Female Undergraduate Biology Education Students - ABUBAKAR, Sunday Ayuba (Ilorin Journal of Education, 2024)
In a bit to affect the student attitude positively and to make the class more interesting, an otherwise theoretical class was restructured into a Cooperative, Flipped, and Digitalized Classroom (CFDC). The study investigated the attitude of undergraduate biology education students taught in a CFDC. A causal-comparative -design was adopted. Purposive sampling was used to sample 64 students (34, male and 30 female). An instrument, Student Attitude Toward Cooperative Flipped Digitalized Classroom (SATCFDC) was used to collect the data for this study. The reliability coefficient of SATCFDC was 0.78 using Cronbach alpha. Data analysis was done using descriptive statistics and an independent sample t-test at a 0.05 significance level. The result showed no significant difference in the attitude of both male and female undergraduate students. It was concluded that CFDC is an activity-driven classroom that enhances a positive attitude among undergraduate students irrespective of gender. Some recommendations were given, which include that the government improve infrastructure to support better internet connectivity to support CFDC.